THE DETERMINATION OF ROLE OF THE YOLK STALK AS A PATHWAY BETWEEN THE YOLK SAC AND INTESTINE USING INDIA INK AS HISTOLOGICAL MARKER IN POST-HATCH BROILER CHICKS - Abrani Sulaiman (Universitas Lambung Mangkurat, 2005)
India ink was used to examine the role of the yolk stalk lumen as a distinct pathway between the yolk sac and gut through the first 5 d of post-hatch growth in broiler chicks. Two hundred and sixteen newly hatched broiler chicks were equally divided into three treatment groups; gavaged via the esophagus (TRT1), injected in the yolk sac (TRT2) with 0.2 mL of water-based black India ink and third group of chicks were used as untreated controls (TRT0). Tissue samples of the small intestine, yolk sac, and yolk stalk were removed and fixed in 10% buffered neutral formalin and were processed routinely, embedded in paraffin, sectioned at 5 to 6 µm, and stained with hematoxylin and eosin. The relative concentration of India ink in each of the tissue preparations was detected with a light microscope and assigned a relative score between 0 and 3, with 0 indicating the lowest and 3 the highest amount of ink present. The results show India ink was able to pass from the yolk sac through the yolk stalk and into the intestine, but was not able to pass from the intestine into the yolk stalk or yolk sac. It was concluded that India ink was useful materials in establishing that the yolk stalk provides a direct one-way passage by which material in the yolk sac may move into the intestine of broiler chicks during the first 5-d after hatching.